Sinonasal Inverted Papilloma Extirpation by Endoscopic Approach: a Case Report - Teuku Husni T.R; Ridha Chaharsyah Mulya (Journal of International Surgery and Clinical Medicine, 2022)
Introduction :Inverted papilloma is a benign tumor that generally arises from the lateral wall of the nasal cavity and mostly grows on the middle meatus.The incidence is rarely found in the ear, throat, nose, throat, head and neck, around 0.5% -4% of all nasal and paranasal sinus tumors.The etiology of inverted papilloma remains unknown.Clinical features of inverted papilloma are unilateral nasal obstruction, rhinorrhea, epistaxis, anosmia, tinnitus and other symptoms.The diagnostic examination are histopathological examinations, CT scans and MRI.Histopathology is the gold standard in diagnosing of inverted papilloma.Management of inverted papilloma is carried out with surgical approach including lateral rhinotomy, maxillectomy, degloving, and non-invasive surgery via endoscopy depend to the krouse classification. Case description : A 44 year-old female patient diagnosed with inverted papilloma was reported.The patient complained of progressiveright nasal obstructionappeared two years ago that turn into total obstruction and rhinorrhea in the last 6 months.A biopsy was done with the result of inverted papilloma. CT scan of the paranasal sinuses showed a mass filling the right nasal cavity, right maxillary sinus and right ethmoid sinus. Patientwas diagnosed with sinonasalinverted papilloma with krouse 2 classificationbased on clinical examination, radiological finding and preoperative endoscopy. Patient was treated with sinonasal inverted papiloma extirpation via endoscopic approach. Conclusion: Inverted papilloma is a benign tumor of the nasal and paranasal sinuses, and biopsy is the gold standard for diagnostic tests. At the same time, the main treatment is done by surgical approachdepend on the krouse classification.